Liver organoids: From fabrication to application in liver diseases - Liu, Qianglin; Zeng, Anqi; Liu, Zibo; Wu, Chunjie; Song, Linjiang (Frontiers in Physiology, 2022)
As the largest internal organ, the liver is the key hub for many physiological processes. Previous research on the liver has been mainly conducted on animal models and cell lines, in which not only there are deficiencies in species variability and retention of heritable material, but it is also difficult for primary hepatocytes to maintain their metabolic functions after in vitro expansion. Because of the increased burden of liver disease worldwide, there is a growing demand for 3D in vitro liver models - Liver Organoids. Based on the type of initiation cells, the liver organoid can be classified as PSC-derived or ASC-derived. Liver organoids originated from ASC or PSC, which are co-cultured in matrix gel with components such as stromal cells or immune cells, and eventually form three-dimensional structures in the presence of cytokines. Liver organoids have already made progress in drug screening, individual medicine and disease modeling with hereditary liver diseases, alcoholic or non-alcoholic liver diseases and primary liver cancer. In this review, we summarize the generation process of liver organoids and the current clinical applications, including disease modeling, drug screening and individual medical treatment, which provide new perspectives for liver physiology and disease research.